On The Double Integral Transform (Complex EE Transform) and Their Properties and Applications - Issa, Ahmad; Kuffi, Emad A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Due to the importance of solutions of partial differential equations, linear, nonlinear, homogeneous, and non-homogeneous, in important life applications, including engineering applications, physics and astronomy, medical sciences, and life technology, and their importance in solutions to heat transfer equations, wave, Laplace equation, telegraph, etc. In this paper, a new double integral transform has been proposed.In this work, we have introduced a new double transform ( Double Complex EE Transform ). In addition, we presented the convolution theorem and proved the properties of the proposed transform, which has an effective and useful role in dealing with the solution of two-dimensional partial differential equations. Moreover, two examples of important mathematical equations are solved to illustrate method. This double  integral transformation has a complex kernel.